Effects of Transcranial Direct Current Stimulation Block Remifentanil-Induced Hyperalgesia: A Randomized, Double-Blind Clinical Trial - Braulio, Gilberto; Passos, Savio C.; Leite, Fabricio; Schwertner, Andre; Stefani, Luciana C.; Palmer, Ana C. S.; Torres, Iraci L. S.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Pharmacology, 2018)
Background: Remifentanil-induced hyperalgesia (r-IH) involves an imbalance in the inhibitory and excitatory systems. As the transcranial Direct Current Stimulation (tDCS) modulates the thalamocortical synapses in a top-down manner, we hypothesized that the active (a)-t-DCS would be more effective than sham(s)-tDCS to prevent r-IH. We used an experimental paradigm to induce temporal summation of pain utilizing a repetitive cold test (rCOLDT) assessed by the Numerical Pain Score (NPS 0-10) and we evaluated the function of the descending pain modulatory system (DPMS) by the change on the NPS (0–10) during the conditioned pain modulation (CPM)-task (primary outcomes). We tested whether a-tDCS would be more effective than s-tDCS to improve pain perception assessed by the heat pain threshold (HPT) and the reaction time during the ice-water pain test (IPT) (secondary outcomes). Methods: This double-blinded, factorial randomized trial included 48 healthy males, ages ranging 19–40 years. They were randomized into four equal groups: a-tDCS/saline, s-tDCS/saline, a-tDCS/remifentanil and s-tDCS/remifentanil. tDCS was applied over the primary motor cortex, during 20 min at 2 mA, which was introduced 10 min after starting remifentanil infusion at 0.06 μg⋅kg-1⋅min-1 or saline. Results: An ANCOVA mixed model revealed that during the rCOLDT, there was a significant main effect on the NPS scores (F = 3.81; P = 0.01). The s-tDCS/remifentanil group presented larger pain scores during rCOLDT, [mean (SD) 5.49 (1.04)] and a-tDCS/remifentanil group had relative lower pain scores [4.15 (1.62)]; showing its blocking effect on r-IH. a-tDCS/saline and s-tDCS/saline groups showed lowest pain scores during rCOLDT, [3.11 (1.2)] and [3.15 (1.62)], respectively. The effect of sedation induced by remifentanil during the rCOLDT was not significant (F = 0.76; P = 0.38). Remifentanil groups showed positive scores in the NPS (0–10) during the CPM-task, that is, it produced a disengagement of the DPMS. Also, s-tDCS/Remifentanil compared to a-tDCS showed lower HPT and larger reaction-time during the IPT. Conclusion: These findings suggest that effects of a-tDCS prevent the summation response induced by r-IH during rCOLDT and the a-tDCS blocked the disengagement of DPMS. Thereby, tDCS could be considered as a new approach to contra-regulate paradoxical mechanisms involved in the r-IH. Clinical trials identification: NCT02432677. URL:https://clinicaltrials.gov/.